The new 'new liberal Indian woman': The glocalization of chick lit. (4th May 2022) - Ghosh, Srijani
ABSTRACT: Since the process of economic liberalization began in India in the 1990s, globalization opened channels for the circulation of Western popular literature and culture in India, which led to their localized adaptation. An illustrative example of this phenomenon is Indian chick lit, which features plots that have a lot in common with Western chick lit but are adapted to reflect urban Indian popular culture, complete with popular Indian stereotypes like the arranged marriage to make it more relatable to the target Indian audience. Through an analysis of Swati Kaushal's Piece of Cake (2004) and Advaita Kala's Almost Single (2009), this essay will illustrate how Indian chick lit represents a newer version of Rupal Oza's post-liberalization 'new liberal Indian woman' and glocalizes the influences of Western culture. I also suggest that Indian chick lit requires a broadening of the understanding of agency to include the choices that privileged subjects make even if they do not dismantle hegemonic power structures.